2007
DOI: 10.1007/s11060-007-9426-z
|View full text |Cite
|
Sign up to set email alerts
|

Delay in radiotherapy shortens survival in patients with high grade glioma

Abstract: Fractionated external beam radiotherapy is an important component of standard treatment for high grade glioma. Due to resource constraints, patients may experience delays in receiving treatment. The purpose of this study was to evaluate the effect of radiotherapy waiting time on survival in patients with high grade glioma. A retrospective analysis was performed of 172 patients with a histological diagnosis of WHO Grade 3 or 4 Astrocytoma who had undergone surgery at Wellington Hospital between 1993 and 2003, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 11 publications
7
81
3
1
Order By: Relevance
“…While most of these studies showed that delay of radiation therapy had no effect on survival, 1,4,9,10 a single study by Irwin et al showed that the risk of death (HR) increased by 8.9% for every week of delay to initiation of radiotherapy. 7 In contrast, however, Blumenthal et al not only found that delay was not associated with worse survival, but that the longest delayed group had the best OS.…”
Section: Discussionmentioning
confidence: 94%
“…While most of these studies showed that delay of radiation therapy had no effect on survival, 1,4,9,10 a single study by Irwin et al showed that the risk of death (HR) increased by 8.9% for every week of delay to initiation of radiotherapy. 7 In contrast, however, Blumenthal et al not only found that delay was not associated with worse survival, but that the longest delayed group had the best OS.…”
Section: Discussionmentioning
confidence: 94%
“…Radical resection in this context is either the surgeons own judgment of per operative radicality or based on radiology, the latter being more sensitive, especially when mRi has been used [10]. The data on high-grade and lowgrade gliomas show a slight increase during recent years, while surgical radicality for meningiomas has been essentially constant.…”
Section: Surgery and Postoperative Radiologymentioning
confidence: 99%
“…By experience, radiological radicality is often more sensitive than the peroperative judgment, and postoperative mRi (within 72 hours) is more sensitive than postoperative CT. The increased use of mRi is encouraging because of its higher sensitivity for brain tumor diagnostics [10]. Postoperative mRi has been the routine in the northern region and the Uppsala region, while the South-eastern region has only recently adopted early postoperative imaging, and this might explain the difference in surgical categorization.…”
Section: Surgery and Radiologymentioning
confidence: 99%
“…Irwin et al retrospectively analyzed the time from surgery to the initiation of RT in 172 patients from 1993 to 2003. 11 They found a mean wait time of 35 days based on multivariate analysis, which was significantly associated with survival with an 8.9% increase in the risk of death per additional week of delay in RT. These results were similar to those of burnet et al, who developed a mathematical model for analyzing the data of patients with glioblastoma and found that delayed RT led to a negative prognosis.…”
Section: Discussionmentioning
confidence: 96%
“…The addition of RT to treatment protocols in three randomized phase III trials demonstrated an approximate doubling of survival and has been the considered standard of care since the late 1970's. [6][7][8] The standard time for RT for most patients is between two and six weeks following surgery 6,[9][10][11][12] ; however, in certain resource-limited centers, it may be as long as…”
mentioning
confidence: 99%